2017
DOI: 10.2174/1573406412666161007150828
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Phyllactone Analogs from the Marine Sponge Phyllospongia papyrecea

Abstract: Background A growing evidence indicates that marine sponge Phyllospongia sp. is one of rich sources of 20, 24-bishomoscalarane sesterterpenes with potent biological activities. In order to search more bioactive 20, 24-bishomoscalarane sesterterpenes for new drug discovery, chemical investigation was carried out on an Indonesian marine sponge P. papyrecea. Methods Bioassay-guided fractionation was carried out on its dichloromethane extract. And nine compounds were purified and isolated using HPLC. Their chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…466) sponges while surprisingly, scalarane-type sesterterpenoids were largely under represented with only one new phyllactone 1175 (Phyllospongia papyracea) reported. 467 Hippolide J was isolated as a pair of enantiomers 1176, 1177 in a non-racemic ratio from the sponge Hippospongia lachne (Yongxing Island, South China Sea). The enantiomers were separable by chiral HPLC with the dextrorotary form (1176) being the more potent antifungal compound against eight strains of hospital-acquired fungi, although both enantiomers exhibit MIC values in the sub mg mL À1 range.…”
Section: Spongesmentioning
confidence: 99%
“…466) sponges while surprisingly, scalarane-type sesterterpenoids were largely under represented with only one new phyllactone 1175 (Phyllospongia papyracea) reported. 467 Hippolide J was isolated as a pair of enantiomers 1176, 1177 in a non-racemic ratio from the sponge Hippospongia lachne (Yongxing Island, South China Sea). The enantiomers were separable by chiral HPLC with the dextrorotary form (1176) being the more potent antifungal compound against eight strains of hospital-acquired fungi, although both enantiomers exhibit MIC values in the sub mg mL À1 range.…”
Section: Spongesmentioning
confidence: 99%
“…The shielded 13 C NMR resonance for phyllolactone B for the methyl attached to C-4 (δ C 17.8 for our sample versus δ C 17.9 for Chang's data 33 ) was indicative of an axial orientation. 27,39 While these data alone indicated that the structures assigned to phyllolactones A−D needed revision, we sought other means to definitively assign the configurations for this bishomoscalarane compound class. Due to our recent success in growing X-ray quality crystals for a variety of natural product terpenoids, 40,41 we decided to undertake similar investigations for phyllolactones A−D.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The afforded extract was dissolved in methanol followed by filtration and subjected to fast separation on a HPLC apparatus (Water D600) equipped with a preparative column (Phenomenex Gemini-NX C18, 50 × 21.2 mm, 5 μm) to afford six fractions F0-F5 using the method described before (Zhang et al, 2017). Then the antimicrobial fraction F4 (0.1547 g) was further separated by semipreparative HPLC with acetinitrile/water (72:28, v/v) to give compounds 1 (35 mg, tR = 13.2 min) and 2 (75 mg, tR = 18.0 min) ( Figure S1).…”
Section: Extraction and Isolation Of Secondary Metabolitementioning
confidence: 99%